Trade Union Activism in the Nordic Countries since 1900
XVIII, 390 p. 8 illus., 1 illus. in color.
Keywords: Providing a Nordic historical perspective, this collection aims to further our understanding of trade union activism and its role in modern society. Contributions from a range of leading scholars analyse the organisational conditions of mobilisation that were deployed by Nordic unionists, and explore the way that they interacted with other forms of social and political protest during the twentieth century. Covering illegal or so-called wildcat strikes, blockades, demonstrations and other activist measures, the authors examine the way that trade union activism in the Nordic countries aimed to move the political combat zone from the meeting rooms of the respective confederations into the streets and the public domain. The collection focuses on cases from Denmark, Sweden, Norway and Finland, but comparisons are also made with countries such as Iceland, Germany, and the USA. Exploring the ways in which political parties have intervened in Nordic trade union activism since the early twentieth century, this unique collection offers new insights for those interested in labour market dynamics and the complex process behind the formation of salary and employment conditions. Jesper Jørgensen is an Archivist and Researcher at the Workers’ Museum and the Labour Movement’s Library and Archives in Denmark. Previously, he studied History and Anthropology at Aarhus University, Denmark. He has recently published on topics like Danish left-wing activism, clandestine communist activities in Scandinavia and the impact of the October Revolution in Denmark. Flemming Mikkelsen holds a Doctorate in Political Science and a MA in History from the University of Copenhagen. He is an independent researcher working in the fields of social movements, labour activism, ethnic relations and historical sociology, and has published several books and articles on these topics, including Popular Struggle and Democracy in Scandinavia, 1700–Present (Palgrave, 2018). Flemming Mikkelsen has studied and taught at the University of Copenhagen, University of Michigan, Aarhus University and Aalborg University.